Predicting in vivo therapeutic efficacy of bioorthogonally labeled endothelial progenitor cells in hind limb ischemia models via non-invasive fluorescence molecular tomography - Lim, Seungho; Yoon, Hong Yeol; Park, Soon-Jung; Song, Sukyung; Shim, Man Kyu; Yang, Suah; Kang, Sun-Woong; Lim, Dong-Kwon; Kim, Byung-Soo; Moon, Sung-Hwan; Kim, Kwangmeyung (ELSEVIER SCI LTD, 2021)
Human embryonic stem cells-derived endothelial progenitor cells (hEPCs) were utilized as cell therapeutics for the treatment of ischemic diseases. However, in vivo tracking of hEPCs for predicting their therapeutic efficacy is very difficult. Herein, we developed bioorthogonal labeling strategy of hEPCs that could non-invasively track them after transplantation in hind limb ischemia models. First, hEPCs were treated with tetraacylated N-azi-domannosamine (Ac4ManNAz) for generating unnatural azide groups on the hEPCs surface. Second, near infrared fluorescence (NIRF) dye, Cy5, conjugated dibenzocylooctyne (DBCO-Cy5) was chemically conjugated to the azide groups on the hEPC surface via copper-free click chemistry, resulting Cy5-hEPCs. The bioorthogonally labeled Cy5-hEPCs showed strong NIRF signal without cytotoxicity and functional perturbation in tubular formation, oxygen consumption and paracrine effect of hEPCs in vitro. In hind limb ischemia models, the distribution and migration of transplanted Cy5-hEPCs were successfully monitored via fluorescence molecular tomography (FMT) for 28 days. Notably, blood reperfusion and therapeutic neovascularization effects were significantly correlated with the initial transplantation forms of Cy5-hEPCs such as 'condensed round shape' and 'spread shape' in the ischemic lesion. The condensed transplanted Cy5-hEPCs substantially increased the therapeutic efficacy of hind limb ischemia, compared to that of spread Cy5-hEPCs. Therefore, our new stem cell labeling strategy can be used to predict therapeutic efficacy in hind limb ischemia and it can be applied a potential application in developing cell therapeutics for regenerative medicine.
Keywords: PLURIPOTENT STEM-CELLS; CLICK CHEMISTRY; TRACKING; PROLIFERATION; TRANSPLANTATION; NANOPARTICLES; RECRUITMENT; HYPOXIA